(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
This article analyzes the concept of intertextuality, with particular interest in the need for limitations to the view that intertextuality is a characteristic of fast fiction. A series of definitions and statements about this resource are listed in short genres. Subsequently, a system of analysis of intertextuality forms used as text construction resources is exemplified. The conclusions focus on the implications of frequent use of these resources in the reading process.